Research of Strategic Alliance Stable Decision-making Model Based on Rough Set and DEA - Zhang Yi (Institute of Advanced Engineering and Science, 2013)
This article uses rough set theory for stability evaluation system of strategic alliance at first. Uses data analysis method for reduction, eliminates redundant indexes. Selected 6 enterprises as a decision-making unit, then select 4 inputs and 2 outputs indexes data, using DEA model to calculate, analysis reasons for poor benefit of decision-making unit, find out improvement direction and quantity for changing, provide a reference for the alliance stability. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3476